Answer:
[tex]h^{l} (s) = \frac{1 }{(\sqrt{s}) (1-\sqrt{s})^{2} }[/tex]
Step-by-step explanation:
Explanation
Given that
[tex]h(s) = \frac{1+\sqrt{s} }{1-\sqrt{s} }[/tex]
Differentiating equation (i) with respective to 'x' ,we get
[tex]h^{l} (s) =\frac{1-\sqrt{s}) \frac{1}{2\sqrt{s} } -(1+\sqrt{s})(\frac{-1}{2\sqrt{s} )} }{(1-\sqrt{s})^{2} }[/tex]
[tex]h^{l} (s) = \frac{\frac{1}{2\sqrt{s} } -\frac{1}{2\sqrt{s} }X\sqrt{s} + \frac{1}{2\sqrt{s} } +\frac{1}{2\sqrt{s} }X\sqrt{s} }{(1-\sqrt{s})^{2} }[/tex]
[tex]h^{l} (s) = \frac{\frac{2}{2\sqrt{s} } }{(1-\sqrt{s})^{2} }[/tex]
[tex]h^{l} (s) = \frac{1 }{(\sqrt{s}) (1-\sqrt{s})^{2} }[/tex]